Reading God's Verses in the Samin Community Tradition in Bojonegoro (An Ecotheological Study) - Nurrohman, Fahrijal; Nazila, Alifia Putri Rochmatun (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
The Samin community in Bojonegoro is one of the communities that, to this day, still maintains and maintains a good relationship with nature. One of their life guidelines is living in moderation (sakcekape). Therefore, they are very careful and careful in managing the environment. From there, it is known that the purpose of writing this article is to examine what traditional practices are still practiced by the Samin community to then be reviewed in an ecotheological study. The method used in this research is qualitative with an interview approach and literature study. From writing this article, the author found that the traditions carried out to this day have a pattern similar to the command to protect nature in the verses of God. The Samin community is very concerned about the continuity of the universe, such as implementing planting seasons according to their seasons. As commanded by Allah SWT in the Qur'an Surah Al-A'raf verse 56. Prof. Quraisy Shihab in his interpretation explains that the prohibition against destroying the earth referred to in this verse is not only about committing sins. Moreover, this verse emphasizes the prohibition against destroying the earth, polluting the environment, and overexploitation. Therefore, indirectly the Samin people have implemented what God said to all mankind.